PROFESSIONAL DEVELOPMENT OF PMRI TEACHERS FOR INTRODUCING SOCIAL NORMS - Ratu Ilma Indra Putri; Maarten Dolk; Zulkardi Zulkardi (Journal on Mathematics Education, 2015)
This paper reports implementation results of designing a workshop for mathematics teacher in introducing classroom social norms. The participants are eight mathematics teachers in primary and junior secondary level. Teachers learned and did some activities about social norms during the workshop. First, they watched an example of learning videos about social norms. Then they discussed and shared in the group about their experiences in using social norms in the classroom. Finally, they made a commitment to try their knowledge about social norms in their classroom. This research used the design research method. Data were collected using videotaped, interview, and focus group discussion and were analyzed qualitatively. Results show that: (1) Teachers satisfied in following all activities relating to the social norms in the workshop. (2) Teachers realized that they had used some activities of social norms such as guiding students to communicate, asking questions and giving argumentation. (3) Teachers have more confidence to use social norms in their mathematics classroom.Keywords: Classroom Social Norms, Teacherâ€™s Workshop, Design Research, PMRIÂ DOI: dx.doi.org/10.22342/jme.61.11